Mechanically tunable curcumin incorporated polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Azad, Lal Busher; Surwase, Sachin S.; Torris, Arun A. T.; Badiger, Manohar V. (Chemistry of Materials, 2016)
We report here on the one-pot synthesis and characterization of curcumin incorporated polyethylene glycol polyurethane (PU-CUR) hydrogels using PEG-4000, 4, 4'-methylenebis (cyclohexyl isocyanate), curcumin in the presence of a cross-linker, 1,2,6 hexanetriol (HT). Besides the physical entrapment, curcumin also provides a partial cross linking in the 3-D structure of the hydrogel. The degree of swelling in hydrogels could be controlled by varying the amount of HT as well as curcumin. The structural characterization of hydrogels was performed using Fourier transform infrared spectroscopy, high-resolution mass spectrometry, UV and fluorescence spectroscopy. The wide-angle X-ray scattering studies revealed the existence of crystalline domains of PEG, and the small-angle X-ray scattering studies showed the presence of lamellar microstructures. Porous structure in the hydrogel was created by cryogenic treatment and lyophilization. Scanning electron microscopy and microcomputed tomography imaging of hydrogels showed the presence of interconnected pores. The mechanical strength of the hydrogels was measured using a universal testing machine. The observed tensile and breaking compression strengths for the equilibrium swollen gels were found to be in the range of 0.22-0.73 MPa and 1.65-4.6 MPa, respectively. Detailed in vitro biological experiments showed the biocompatibility of gels, cytostatic dosage of curcumin, selective toxicity toward cancer cell lines, and antibacterial property. These gels show promising applications as scaffolds and implants in tissue engineering.

Mechanism of the formation of microphase separated water clusters in a water-mediated physical network of perfluoropolyether tetraol - Deshpande, Ashwini A.; Torris, Arun A. T.; Pahari, Swagata; Menon, Shamal K.; Badiger, Manohar V.; Rajamohanan, P. R.; Wadgaonkar, Prakash P.; Roy, Sudip; Tonelli, Claudio (Soft Matter, 2018)
Perfluoropolyether tetraol (PFPE tetraol) possesses a hydrophobic perfluoropolyether chain in the backbone and two hydroxyl groups at each chain terminal, which facilitates the formation of hydrogen bonds with water molecules resulting in the formation an extended physical network. About 3 wt% water was required for the formation of the microphase separated physical network of PFPE tetraol. The mechanism responsible for the microphase separation of water clusters in the physical network was studied using a combination of techniques such as NMR spectroscopy, molecular dynamics (MD) simulations and DSC. MD simulation studies provided evidence for the formation of clusters in the PFPE tetraol physical network and the size of these clusters increased gradually with an increase in the extent of hydration. Both MD simulations and NMR spectroscopy studies revealed that these clusters position themselves away from the hydrophobic backbone or vice versa. The presence of intra-and inter-chain aggregation possibility among hydrophilic groups was evident. DSC results demonstrated the presence of tightly and loosely bound water molecules to the terminal hydroxyl groups of PFPE tetraol through hydrogen bonding. The data from all the three techniques established the formation of a physical network driven by hydrogen bonding between the hydrophilic end groups of PFPE tetraol and water molecules. The flexible nature of the PFPE tetraol backbone and its low solubility parameter favour clustering of water molecules at the terminal groups and result in the formation of a gel.